Implantation initiation of self-assembled embryo-like structures generated using three types of mouse blastocyst-derived stem cells - Shaopeng Zhang (Nature Portfolio, 2019)
The precise cellular patterning and decisions of early embryogenesis have been hard to mimic in vitro. Here, the authors culture murine embryonic and trophoblast stem cells together with extra-embryonic endoderm stem cells to form embryo-like structures (ETX-embryoids), which can initiate an implantation response.